2008
DOI: 10.1016/j.jpainsymman.2007.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Disclosure Through Patient Narrative May Improve Pain and Well-Being: Results of a Randomized Controlled Trial in Patients with Cancer Pain

Abstract: Narrative medicine is based upon physicians' awareness of patients' narration of their suffering, their hopes, and how illness has affected them. It offers a model for improving health outcomes. To determine whether incorporating a narrative approach in patients with cancer decreases pain intensity and improves their global sense of well-being, we performed a randomized, single-blind controlled trial in adult patients with cancer and average pain intensity levels of at least 5/10. Two hundred thirty-four patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 33 publications
1
68
0
2
Order By: Relevance
“…Of the 64 included studies, 9,51-58,66-119 59 9,51,[54][55][56][57][58][66][67][68][71][72][73][74][75][76][77][79][80][81][82][83][84][85][86]88,89,91, were RCTs, and four 52,78,87,92 were non-randomised studies. The remaining study 53 was a matched case-control study.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 64 included studies, 9,51-58,66-119 59 9,51,[54][55][56][57][58][66][67][68][71][72][73][74][75][76][77][79][80][81][82][83][84][85][86]88,89,91, were RCTs, and four 52,78,87,92 were non-randomised studies. The remaining study 53 was a matched case-control study.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…Among those, numerical results were derived from graphs in nine studies. 51,53,56,70,85,103,110,114,121 Several studies under-reported the numerical data (e.g. reporting the mean with no measure of variability, such as the SD) or used different statistics [such as the median, together with confidence intervals (CIs) and/or ranges or the mean together with the SE] to report the results.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These qualities should be integrated into the interaction and are more important to patient outcomes than the actual verbiage of the discussion (Coulehan & Block, 2006). With an empathetic listener, the retelling of a medical trauma can itself be therapeutic (Cepeda et al, 2008). This exchange also provides the AP obtaining the history with an opportunity to establish a bond with a new patient and his or her family members and to assess the patient's emotional response to the cancer diagnostic process.…”
Section: History Of the Present Illnessmentioning
confidence: 99%